Evidence of intermittent exercise of high intensity, strength or combined; using the variationof the response to develop effective and accurate medicine (Revista horizonte, 2021)
Introduction. Although the wide variability to exercise has been studied, there are few studies that have addressed the existence of this phenomenon using different exercise modalities. Objective: To investigate which including 20-cardiometabolic or performance variables respond well (improve) after intermittent exercise (HIT), strength (RT) or combined exercise (CT). Methodology: Forty-five adult women with insulin resistance were distributed in four groups (HIT, 39.2 ± 9.5 years, BMI, 29.3 ± 3.3, N = 14), (RT, 33.9 ± 9.3 years, BMI, 29.4 ± 5.5, N = 8), (CT, 43.3 ± 8.1 years,BMI, 29.1 ± 2.9, N = 10); and a control group (CG, 40.1 ± 11.4 years, BMI, 28.3 ± 3.5, N = 13). Body composition variables (N = 9), cardiovascular (N = 3), metabolic (N = 3), and performance variables (N = 5 variables) were measured before and after the intervention, responders and non-responders were reported. Results: The RT exercise showed a lower number of subjects NRs, versus HIT or CT. Significant changes were recorded in body composition, metabolic parameters and endurance performance. Conclusion: Considering 20 variables as objective, and including 3 types of exercise, independently of the volume and frequency of the exercise, the RT exercise offers a greater capacity to improve 20 variables, offering a smaller number of subjects NRs. Additionally, both HIT and RT promote more benefits versus CT to improve body composition, cardiovascular and metabolic parameters.